Evaluation of Land Use Change in Kiboko Watershed, Kenya - Mutai , E. B. K.; Obiero , J. P.; Ruttoh , R. C.; Toromo , A. K. (African Journal of Education,Science and Technology (AJEST), 2014)
The Kiboko watershed has undergone changes in land use in the recent past which is suspected to have caused degradation by soil loss. The changes in the land use were quantified through a comprehensive land use change detection carried out between 1980 and 2009 for Kiboko Watershed, using Geographic Information Systems (GIS). This was achieved through spatial analysis on each of the land use map and statistical analysis by means of an overlay operation to examine land use pattern in the watershed. The results showed that both Irrigated and cultivated land increased from 0Ha (0%) in 1980 to 395Ha (0.1%) and 16,955Ha (3%) in 2009 respectively, while shifting cultivation, rangeland, and residential land increased from 10,784Ha (2%), 568,7657Ha (88%) and 0Ha (0%), in 1980 to 16,955Ha (3%), 574,502Ha (89%), and 773Ha (0%) in 2009 respectively. In the same period, agro-pastoralism decreased from 66,206 Ha (10%) to 22,680Ha (4%). It can be concluded that the area under cultivation for crop production and residential land are on increasing trend while that of range land is on a decreasing trend.